Post-emergence herbicides efficacy for weed management in kharif maize (Zea mays) - RADHESHYAM, RADHESHYAM; JAT, S L; PARIHAR, C M; SINGH, A K; POONIYA, V; SINGH, RAJ (The Indian Journal of Agricultural Sciences, 2021)
The escalating labour prices have significantly increased the production cost of kharif maize in India. To addressthis, a field experiment was conducted (2017) to evaluate the efficacy of post-emergence herbicide in kharif maize(Zea mays L.) at ICAR-Indian Institute of Maize Research, Pusa Campus, New Delhi. The tank-mix post-emergenceherbicide application, viz. tembotrione (120 g/ha) or topramezone (25.2 g/ha) at 15 DAS with 75% atrazine (750 g/ha) or as a sequential application at 25 DAS after pre-emergence (PE) 75% atrazine gave significant weed control inkharif maize by reducing density and dry weight. Significantly higher weed-control efficiency, weed-control index,herbicide efficiency index and lower weed persistence index were found in weed-free check, which was at par withPE atrazine (1000 g/ha) followed by hand weeding at 25 DAS and the post-emergence herbicide application oftembotrione (120 g/ha) /topramezone (25.2 g/ha) as tank-mix with 75% atrazine dose as early post-emergence at 15DAS or as the sequential application of these combinations. Significantly lowest weed index was observed in thesequential application of tembotrione/topramezone at 25 DAS after 75% atrazine dose as PE while the highest weedindex (49.3) with alone halosulfuron application. It was concluded that the application of post-emergence herbicide,viz. tembotrione (120 g/ha) /topramezone (25.2 g/ha) as tank-mix at 15 DAS with 75% dose of atrazine (750 g/ha)or as a sequential application at 25 DAS after 75% atrazine as PE found promising for better weed control and grainyield in kharif maize.